IMPLEMENTATION OF SUBSURFACE INVESTIGATION METHODS ON ROTMISTROVKA IMPACT CRATER IN ORDER TO STUDY ITS GEOLOGICAL AND GEOCHEMICAL FEATURES - Semenuk, V.G. (Institute of Geological Sciences, NAS of Ukraine, 2016)
In order to study the geological structure of Rotmistrovka impact crater and presence of gas within it, the complex of structural-thermo-atmogeochemical research (STAGR) was conducted. For the first time satellite image interpretation of impact crater area was carried out that make it possible to clarify its structure. Applying of the complex of field, laboratory and analytical works provides identifying of thermo-atmogeochemical characteristics of fields. Based on the correlation analysis of the relationship between the components of certain gases, promising areas in search of hydrocarbon accumulations was allocated.